Antioxidant activity coefficient, mechanism, and kinetics of different derivatives of flavones and flavanones towards superoxide radical - Safeer AHMED; Faria SHAKEEL (Czech Journal of Food Sciences, 2012)
A systematic investigation of the electrochemically generated superoxide radical (O2●-) has been conducted in the presence of some flavonoids. Cyclic voltammetry was used to generate O2●- by reducing the molecular oxygen in DMSO at room temperature. The scavenging of the radical was monitored by the decrease in anodic or/and cathodic currents while linearly increasing the concentration of the flavonoid. The strength of interaction was quantified in terms of the binding constant (Kb)values ranging from 1 × 102 and 5 × 103M-1. The antioxidant activity coefficient (Kao) was calculated from the linear part of the plot of 'current decrease vs. flavonoid concentration'. Radical scavenging mechanism of the antioxidant was proposed and discussed in terms of the structure activity relationship. Nicholson-Shain method was employed to estimate the bimolecular homogeneous kinetics and on this basis control use of antioxidant is pointed out.